P175 Domiciliary visits by specialist respiratory clinicians for patients with COPD: patient experience, outcomes and predicting those that may benefit most. (12th November 2019) - Linacre, E; Ryan, K; McDonnell, L; Dewar, A
Abstract : Introduction and objectives: The Integrated Respiratory Team aims to provide holistic individualised care for patients with COPD. Patients who are housebound, frail, or assessed as needing intensive 1:1 support for self-management, receive domiciliary visits, with the aims of improving patient self-management, and preventing admission to hospital. Methods: Patients (n=20) were assessed with PHQ9, GAD7 and EQ5D5L questionnaires during the visit, followed by a structured telephone interview within one week. Patients were excluded if they were unable to complete telephone interview. Results: Participants: 9 female: 11 male, mean age 74 years (range 62 to 91), mean MRC score 4.7. 5 patients were GOLD II, 12 patients GOLD III and 3 patients GOLD IV. Patient-reported experience: 100% of patients reported the visit took place at a suitable time; 90% reported they felt they definitely had enough time to discuss what was required; and 93% felt that the right amount of information was provided. Patient-reported outcome: 95% of patients rated the domiciliary visit as ' Very useful' . When asked if they ' felt confident they could self-manage their condition' after domiciliary visit, 50% of patients responded ' Yes definitely ', 45% responded ' Yes to some extent ', and 5% responded ' No '. Qualitative answers also provided strongly positive responses. Predicting benefit: matched Wilcoxon signed rank test was used to investigate correlation between PHQ9, GAD 7 and EQ5D5L scores and patient reported confidence in their ability to self-manage their condition after domiciliary visit. GAD7 and PHQ9 scores did not correlate with the patients' self-reported confidence in self-managing their condition. Higher EQ5D5L score did show significant correlation with self-reported confidence in their ability to self-manage after domiciliary visit p<0.001. Conclusion: Patients with poorer health-related quality of life were most likely to feel confident in their ability to self-manage after a domiciliary visit. Interventions that improve self-management have been concluded to reduce respiratory-related and all-cause admissions, reduce dyspnoea and improve quality of life [1]. Models of care that allow specialist domiciliary visits may be important in improving outcomes for patients with poorer health-related quality of life. Reference: Zwerik M, et al . Self-management for patients with COPD. Cochrane Database Syst Rev 2014;3:CD002990.